KONTRIBUSI ISTRI DALAM PEREKONOMIAN KELUARGA DI KABUPATEN MAJENE PERSPEKTIF MAQĀṢID AL-SYARĪ‘AH - Supriadi Supriadi; Nur Astaman Putra; Mustafa Mustafa; Muljan Muljan; Fajar Fajar (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
This study examines the contribution of wives to family economic welfare from the perspective of maqāṣid al-sharī‘ah in Majene Regency. The research employed a field study approach involving female street vendors at the Central Market of Majene. Ushul fiqh, sociological, and philosophical approaches were utilized, while data were collected through observation, interviews, and documentation and analyzed using descriptive qualitative methods. The findings reveal that wives’ participation in family economic activities is driven by economic demands and the local cultural value of sibali parri’, which emphasizes cooperation between spouses. Women play not only domestic roles but also significant economic roles in maintaining household stability. Their contribution positively affects family welfare, resilience, egalitarian relationships, and the fulfillment of basic family needs. From the perspective of maqāṣid al-sharī‘ah, such participation aligns with the objectives of Islamic law, particularly the protection of wealth (ḥifẓ al-māl), life (ḥifẓ al-nafs), and family sustainability. However, the dual burden experienced by working wives remains a major challenge that requires a more equitable distribution of household responsibilities.